An Application Of Guided Inquiry Method And Simple Media To Improve The Studentsâ Learning Interest And Achievement Of Math On Addition And Subtracttion Of Three Numbers For Third Graders Of Sd Negeri 2 Pagedangan - Suratmi, Suratmi (Universitas Muhammadiyah Purwokerto, 2014)
The study was aimed at improving the studentsâ learning interest and achievement ofmath on topic of addition and subtraction of three numbers though a work group as thetechnique to improve the learning process. It applied a classroom action researchconducted following the principles of Kemmis S, C Taggart R (1988) coveringplanning, acting, oberserving, and reflecting or evaluating. These stages were donerepeatedly and made into cycles. This was done by collaborating with the peers asobserver, supervisor and the principal of the elementary school.Based on the analysis, it can concluded that (1) the studentsâ interest in attending thelearning is better than the coventional method, by applying the guided inquiry and thesimple media, (2) the studentsâ learning achievement also improves, by applying themethod and the simple media. This can be seen from the increase of studentsâ learninginterest from the cycle I. It was 62% and their learning mastery was 63,38% , with anaverage score of 70,07. At the end of the Cycle II, their learning interest improved to82,4%. Their learning mastery was 88,46% and their average score was 78,26. Based onthe findings, it can be concluded that the learning of math on addition and subtractionusing guided inquiry method can be successfully applied in a classroom action research.Keywords: guided inquiry method, simple media, interest, achievement.